Interdisciplinary Curriculum Development and Strengthening Moderate Islam as the Future Direction for Islamic Religious Higher Education Institutions (PTKI) in Indonesia - Nafi Lutfi ‘Ulia Ristiana; Dwi Ratnasari (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2026)
The change of Islamic Religious Universities (PTKI) in Indonesia from State Islamic Religious Colleges (STAIN) and State Islamic Religious Institutes (IAIN) to State Islamic Universities (UIN) opens a new era for the development of science based on Islamic values. However, this institutional transformation has not been fully able to answer the challenges of globalization, digitalization, and increasing social and religious polarization. PTKI is required  not only to produce graduates who excel academically, but also to have an inclusive, critical, and moderate religious character. This article aims to analyze the future direction of PTKI through two strategic pillars, namely the development of an interdisciplinary curriculum and the strengthening of moderate Islam. This research uses a literature study approach by examining various relevant scientific sources. The results of the study show that the integration of religious science and general science is not only to reduce the scientific dichotomy, but to build a complementary scientific and religious perspective. The interdisciplinary curriculum paradigm allows students to examine religious and social issues through various scientific perspectives, thereby encouraging academic dialogue, intellectual tolerance, and strengthening critical thinking. Other findings reveal that the internalization of wasathiyah values (religious moderation) will be more effective if it is not only taught through courses, but also instilled through campus ecosystems, academic culture, and scientific practices. This study recommends that PTKI strengthen the relevance of curriculum, learning innovation, and moderate academic culture as a strategy for developing Islamic education that is superior, inclusive, and globally competitive.